Analisis Validitas Lembar Kerja Peserta Didik Berbasis Multiple Inteligences - Muh Nur Iqramsyar; Rukli Rukli; Agustan Agustan (Institut Agama Islam Negeri Palopo, 2022)
The research aims to analyze the validity of the high-intelligent learner's worksheet. This study helps in producing a worthwhile innovation product used in learning, which is the intelligence-oriented sheet of each learner to increase the learning result. The study uses an exploratory type method that focuses on the multiage-based learner's worksheet with the objective of seeing and measuring in-depth worthiness on the multi-intelligence intelligence learner's worksheet through the expert validator and practitioners. This research can be used as a model for research and development (r & D), so the multi-intelligence intelligence resource worksheet that was developed is worthy of use. In the analysis, there were three validators, consisting of one expert validator and two practitioners. To analyze the feasibility of the multi-intelligence learner's worksheet, we used validation questionnaire. Based on valification analysis and instrument charging data by expert tests and good practitioners of design and materials, it suggests that the multi-intelligence intelligence education worksheet is judged with an average score of 4.66, which is perfectly valid. So it can be concluded that the high-intelligence learners' worksheets can be used in learning.